Fecundidad y época de desove del arenque hebra opisthonema libertate (Pisces: Clupeidae) en el Golfo de Nicoya, Costa Rica. (ING) - Rodríguez, Jorge A.; Palacios, José A; Chavarría, Ana (Uniciencia, 1986)
The thread herring Opisthonema libertate Spawns year round with a maximum between December-March. The sex ratio was stadisticaly different only in May, September and December therefore; any sex could predominate in the commercial capture.The lineal regression between number of oocites and total length was Y = 722 x - 111,200 (r = 0.5 P < 0,01) and between number of oocites and weight was Y = 395+4,154 ( r = 0,45 P < 0,01 ). There was a high variation in the number of oocites with the same lengths or weights. Average relative fecundity by fish gram was 412,16 eggs between 1985-1986